Family Foster Care Coordinator and His Role in Foster Care System - Tomasz Gebel (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The purpose of the article is the discussion about new profession - family foster care coordinator. The author presents work dimensions of the foster care coordinator which results both from statutory assumptions and those related to tasks that go beyond upbringing. The professionalisation of the family foster care coordinator is an important element of effective support of the foster care system.